INTEGRATION PLANNING BETWEEN COMPONENTS OF TYPE B BUS STATION SUKOREJO - Handayani, Sabrina; Afriyanti, Dessy Angga; Al Fauzi, Egista Wima (Journal of Applied Engineering Science, 2024)
Kendal Regency has problems with passenger bus station services in the transportation sector. Integrating components in Sukorejo Type B Bus Station includes crossing circulation patterns between people and vehicles. The crossing can cause conflicts that endanger the safety of service users. This study aimed to handle circulation conflicts through the integration of the components applied in the Sukorejo Type B Bus Station can be optimal. This study used a methodological approach such as quantitative, explanation, and planning, referring to the field results and observational surveys. This research used 135 respondents of inter-city transportation within the province (AKDP) and 147 respondents of rural transportation (ANGDES). The results showed the integration performance between the components of the Sukorejo Type B Bus Station through the Normalized Score, which got a value of -100 with good information and indicated by the total circulation distance needed to reach each bus station component in 452 meters for 342 seconds. In Bus Station Type B Sukorejo, circulation crossings caused conflict at as many as 10 points due to the pedestrian crossing activities in private vehicle parking, arrival areas, waiting areas, and public transport departures. The research value of PV2 < 108 meant the need for pedestrian facilities indicated that it was not necessary to handle circulation crossings with pedestrian facilities. It was just sufficient to provide pedestrian warning signs to cross, so that vehicle drivers could be careful in crossing each conflict point.
Keywords: integration, bus station, pedestrian